2005
DOI: 10.1007/s00024-005-2712-9
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of the Gravity and Magnetic Anomalies of the Cappadocia Region, Central Turkey

Abstract: The Cappadocia region, located in Central Turkey, is characterized by widespread lava flows and volcanoclastic deposits dating from Miocene to Quaternary. Gravity and aeromagnetic anomalies of the region appear to present similar high and low amplitude regions, although the aeromagnetic anomalies exhibit a rather complex pattern which is thought to be caused by remanent magnetization. The low-pass filtered aeromagnetic map shows a deep-seated magnetic anomaly which may be linked to the widespread volcanic acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 17 publications
1
25
0
Order By: Relevance
“…Calis, Karacadag and Deliler volcanites), which resulted from the tectonic movements that occurred at different times throughout the geological history, are outcropped in limited areas and are also encountered as intercalations with sedimentary deposits. The age (Late Cretaceous, Mid-Late Eocene and Late MioceneQuaternary) of these volcanic rocks is identical to the main tectonic periods in the Central Anatolia (Dincer, 1978;Dellaloglu, 1991;Buyuksarac et al, 2005).…”
Section: Geological Settingmentioning
confidence: 67%
See 1 more Smart Citation
“…Calis, Karacadag and Deliler volcanites), which resulted from the tectonic movements that occurred at different times throughout the geological history, are outcropped in limited areas and are also encountered as intercalations with sedimentary deposits. The age (Late Cretaceous, Mid-Late Eocene and Late MioceneQuaternary) of these volcanic rocks is identical to the main tectonic periods in the Central Anatolia (Dincer, 1978;Dellaloglu, 1991;Buyuksarac et al, 2005).…”
Section: Geological Settingmentioning
confidence: 67%
“…There are some other obvious anomalies in Fig. 5, such as the anomaly to the south of Konya studied by Ates and Kearey (2000), the other one to the east of Aksaray studied by Buyuksarac et al (2005) and the last one to the north of Kaman. However, their lo- cations are beyond the boundaries of the Tuzgolu and Haymana Basins and as such are not the subject of this study.…”
Section: Aeromagnetic Datamentioning
confidence: 86%
“…Reasons and examples of complexity in the filtering process were given by Kearey (1991) and Buyuksarac et al (2005). The crustal thickness map produced from the low-pass filtered gravity anomalies of Turkey is given in Fig.…”
Section: Gravity Anomalies and Interpretationmentioning
confidence: 99%
“…In the Eastern Anatolia region, BEKTAS et al (2007) showed that the Curie point depth fluctuated between 12.9 and 22.6 km. BUYUKSARAC et al (2005) identified a rotational effect in Cappadocia region, and found good correlation between magnetic anomalies and anticlockwise rotations. On the other hand, BUYUKSARAC (2007) investigated the regional wrench tectonics of inner East Anatolia (Turkey) using potential field data and exhibited similarities between tectonic lineaments of inner East Anatolia and the direction of the East Anatolian Fault Zone.…”
Section: Previous Crustal Structure Investigations In Turkeymentioning
confidence: 99%